1976
DOI: 10.1016/0006-8993(76)90334-6
|View full text |Cite
|
Sign up to set email alerts
|

Transfer characteristics of first and second order lateral canal vestibular neurons in gerbil

Abstract: Discharge patterns of first and second order vestibular neurons responding to angular acceleration in the plane of the lateral canals were studied in gerbil. The resting discharge activity of each cell was used to characterize the neuron by measureing the coefficient of variation and coefficient of skewness of the interspike interval distributions. Sinusoidal angular oscillations ranging in frequency from 0.0125 to 5.0 Hz were delivered by a velocity controlled rate-table. A PDP-12 minicomputer system was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 10 publications
3
31
0
Order By: Relevance
“…Note that the average responses of low-gain irregular afferents rise to match those of high-gain irregular afferents at high frequencies. Curthoys 1982;Dickman and Correia 1989b;Fernandez and Goldberg 1971;Goldberg and Fernandez 1971;Haque et al 2004;Landolt and Correia 1980;O'Leary et al 1976;Schneider and Anderson 1976;Tomko et al 1981;Yagi et al 1977). A regression between each afferent's CV* and each of the two time constants making up the two-zero lead operator best fitting its responses was performed.…”
Section: Calculation Of Lead Operator and Transfer Function Fitsmentioning
confidence: 99%
“…Note that the average responses of low-gain irregular afferents rise to match those of high-gain irregular afferents at high frequencies. Curthoys 1982;Dickman and Correia 1989b;Fernandez and Goldberg 1971;Goldberg and Fernandez 1971;Haque et al 2004;Landolt and Correia 1980;O'Leary et al 1976;Schneider and Anderson 1976;Tomko et al 1981;Yagi et al 1977). A regression between each afferent's CV* and each of the two time constants making up the two-zero lead operator best fitting its responses was performed.…”
Section: Calculation Of Lead Operator and Transfer Function Fitsmentioning
confidence: 99%
“…Discharge properties of vestibular-nerve fibers have been described in several mammals FernĂĄndez 1971a, 1971b;FernĂĄndez and Goldberg 1971, 1976a, 1976bSchneider and Anderson 1976;Baird et al 1988;Goldberg et al 1990a;Lysakowski et al 1995) and in selected lower vertebrates, including the toadfish (Boyle and Highstein 1990a), frog (Honrubia et al 1989;Myers and Lewis 1990), and turtle Goldberg 1996, 2000a). In most of these species, it has proved useful to distinguish afferents as having a regular or an irregular spacing of action potentials (Fig.…”
Section: Peripheral Mechanisms Discharge Regularity and Other Discharmentioning
confidence: 99%
“…These authors also reported on the sensitivity versus frequency relationship of central vestibular neurons in the same preparation (Jones and Milsum 1971). Their findings were expanded by subsequent investigators in nonprimate species (Broussard et al 2004;Schneider and Anderson 1976;Shinoda and Yoshida 1974) and in alert monkeys (Buttner et al 1978;Cullen and McCrea 1993;Dickman and Angelaki 2004;Fuchs and Kimm 1975;Keller and Kamath 1975;Ramachandran and Lisberger 2008). Most of these studies concerned the effect of frequency on the sensitivity and phase of responses of individual neurons and demonstrate a relatively flat relationship for frequencies between 0.1 and 2.0 Hz with an increasing phase lead relative to velocity as the frequency of rotation increases.…”
mentioning
confidence: 79%
“…Thus very high sensitivity with low-stimulus amplitudes allow for detection of low-amplitude signals over the inherent noise from the spontaneous activity of these cells. Although we did not calculate the regularity of firing rate of these cells, others have noted that second-order vestibular neurons fire with a range of regularity, but on the whole demonstrate more irregularity than afferents because there is no population of central neurons as regularly firing as regular afferents (Chen-Huang et al 1997;Iwamoto et al 1990;Schneider and Anderson 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation